Progression of lumbar disc degeneration over a decade: a heritability study. Issue 7 (13th March 2011) - Williams, Frances M K; Popham, Maria; Sambrook, Philip N; Jones, Annette F; Spector, Tim D; MacGregor, Alex J
Abstract : Objectives: Lumbar disc degeneration (LDD) is prevalent, age-related and contributes to low back pain. Cross-sectional LDD as determined by MRI scan is known to be highly heritable. The authors postulated that the rate of progression might also be controlled by genetic factors. Methods: A 10-year follow-up of MRI-determined LDD was performed in 234 pairs of twin volunteers in the UK and Australia, comprising 90 monozygotic pairs and 144 dizygotic same-sex twin pairs. Of the total sample, 95% were female. The mean age at baseline was 53.3 years (range 32.3–69.5). The rate of progression was calculated and, because the effect of age was non-linear, the sample was divided into age strata and heritability estimated for each trait's progression. Results: All MRI-determined traits worsened significantly over the period of follow-up (p<0.0001 for each). Change in disc height was not heritable at any age while posterior disc bulge was heritable across all age categories (range 28–53%), with higher heritability in those over 60 years. Change in disc signal intensity and anterior osteophytes were found to be heritable only in those aged under 50 years at baseline (heritability estimates 76% (95% CI 44% to 100%) and 74% (42% to 100%), respectively). Conclusions: Longitudinal change in LDD traits is heritable for all traits except disc height, but there is a significant influence of age, which varies across traits. Future studies to define the genetic variants influencing LDD progression should examine MRI traits individually and in women should focus on those under 50 years of age.